Targeting the upstream transcriptional activator of PD-L1 as an alternative strategy in melanoma therapy - Zhu, B; Tang, L; Chen, S; Yin, C; Peng, S; Li, X; Liu, T; Liu, W; Han, C; Stawski, L; Xu, Z; Zhou, G; et al. (Springer Nature, 2018)
Programmed cell death ligand 1 (PD-L1) interacts with programmed cell death protein-1 (PD-1) as an immune checkpoint. Reactivating the immune response by inhibiting PD-L1 using therapeutic antibodies provides substantial clinical benefits in many, though not all, melanoma patients. However, transcriptional suppression of PD-L1 expression as an alternative therapeutic anti-melanoma strategy has not been exploited. Here we provide biochemical evidence demonstrating that ultraviolet radiation (UVR) induction of PD-L1 in skin is directly controlled by nuclear factor E2-related transcription factor 2 (NRF2). Depletion of NRF2 significantly induces tumor infiltration by both CD8+ and CD4+ T cells to suppress melanoma progression, and combining NRF2 inhibition with anti-PD-1 treatment enhanced its anti-tumor function. Our studies identify a critical and targetable PD-L1 upstream regulator and provide an alternative strategy to inhibit the PD-1/PD-L1 signaling in melanoma treatment.